Policy Analysis of MaaS (Mobility-as-a-Service) in the Context of Sustainable Tourism in Ubud Tourist Destination - I Putu Angga Darata Zunaeca; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research analyzes the developing Mobility-as-a-Service (MaaS) policy in the Ubud tourism destination, aiming to support sustainable tourism. Using a qualitative descriptive approach, data was collected through interviews, observations, and document studies. The findings indicate that MaaS has the potential to improve public transportation integration, reduce traffic congestion, and lower the carbon footprint of tourists. However, challenges were found in three key areas: inter-agency coordination, user awareness, and digital infrastructure. This policy shows a positive direction toward an environmentally friendly and inclusive tourist transportation system. However, it requires a stronger institutional framework and cross-sector support to be effective.